Health related quality of life among Rheumatic Fever and Rheumatic Heart Disease patients in India. - Jyoti Dixit (Public Library of Science (PLoS), 2021)
Background Measurement of health-related quality of life (HRQOL) of people with chronic illnesses has become extremely important as the mortality rates associated with such illnesses have decreased and survival rates have increased. Thereby, such measurements not only provide insights into physical, mental and social dimensions of patient's health, but also allow monitoring of the results of interventions, complementing the traditional methods based on morbidity and mortality. Objective The present study was conducted to describe the HRQOL of patients suffering from Rheumatic Fever (RF) and Rheumatic Heart Disease (RHD), and to identify socio-demographic and clinical factors as predictors of HRQOL. Methodology A cross-sectional study was conducted to assess the HRQOL among 702 RF and RHD patients using EuroQol 5-dimensions 5-levels instrument (EQ-5D-5L), EuroQol Visual Analogue Scale and Time Trade off method. Mean EQ-5D-5L quality of life scores were calculated using EQ5D index value calculator across different stages of RF and RHD. Proportions of patients reporting problems in different attributes of EQ-5D-5L were calculated. The impact of socio-economic determinants on HRQOL was assessed. Results The mean EQ-5D-5L utility scores among RF, RHD and RHD with Congestive heart failure patients (CHF) were estimated as 0.952 [95% Confidence Interval (CI): 0.929-0.975], 0.820 [95% CI: 0.799-0.842] and 0.800 [95% CI: 0.772-0.829] respectively. The most frequently reported problem among RF/RHD patients was pain/discomfort (33.8%) followed by difficulty in performing usual activities (23.9%) patients, mobility (22.7%) and anxiety/depression (22%). Patients with an annual income of less than 50,000 Indian National Rupees (INR) reported the highest EQ-5D-5L score of 0.872, followed by those in the income group of more than INR 200,000 (0.835), INR 50,000-100,000 (0.832) and INR 100,000-200,000 (0.828). Better HRQOL was reported by RHD patients (including RHD with CHF) who underwent balloon valvotomy (0.806) as compared to valve replacement surgery (0.645). Conclusion RF and RHD significantly impact the HRQOL of patients. Interventions aiming to improve HRQOL of RF/RHD patients should focus upon ameliorating pain and implementation of secondary prevention strategies for reducing the progression from ARF to RHD and prevention of RHD-related complications.